Perioperative Levels of IL8 and IL18, but not IL6, are Associated with Nucleus Basalis Magnocellularis Atrophy Three Months after Surgery - Maria Heinrich; Claudia Spies; Friedrich Borchers; Insa Feinkohl; Tobias Pischon; Arjen J. C. Slooter; Clarissa von Haefen; Norman Zacharias; Georg Winterer; Florian Lammers-Lietz (Journal of Neuroimmune Pharmacology, 2024)
Past studies have observed that brain atrophy may accelerate after surgical procedures. Furthermore, an association of systemic inflammation with neurodegeneration has been described. We hypothesize that postoperative interleukin (IL) levels in circulation as well as the perioperative change in interleukin levels are associated with increased postoperative atrophy in the Nucleus basalis magnocellularis (of Meynert, NBM) which is the major source of cortical acetylcholine. We analyzed data from the BioCog cohort which included patients ≥ 65 years presenting for elective major surgery (≥ 60min). Blood samples were taken before surgery and on the first postoperative day. Magnetic resonance imaging of the brain and neuropsychological assessments were conducted before surgery and after three months follow-up. We used linear regression analysis to determine the association of three interleukins (IL6, IL8 and IL18) with NBM atrophy (in % volume change from baseline before surgery to follow-up), as well as to examine the associations of NBM atrophy and volume with postoperative cognitive ability and perioperative cognitive change. Receiver-operating curves were used to determine the prognostic value of preoperative interleukin levels. For IL8 (N = 97) and IL18 (N = 217), but not IL6 (N = 240), we observed significant associations of higher postoperative IL levels at the first postoperative day with higher NBM atrophy at three months after surgery. Subsequent analyses suggested that in both IL8 and IL18, this association was driven by a more general association of chronically elevated IL levels and NBM atrophy, reflected by preoperative IL concentrations, rather than IL response to surgery, measured as the difference between pre- and postoperative IL concentrations. At follow-up, NBM volume was positively associated with the level of cognitive performance, but NBM atrophy was not significantly related to perioperative cognitive change. Prognostic value of preoperative IL concentrations for NBM atrophy was low. Our results suggest that an association of postoperative interleukin levels with NBM atrophy is driven by preoperatively elevated interleukins due to pre-existing inflammation, rather than perioperative change in interleukin levels in response to surgery and anesthesia. The BioCog study has been registered at clinicaltrials.gov on Oct 15, 2014 (NCT02265263). Graphical Abstract